2024
DOI: 10.1038/s41420-024-01863-1
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis: a new hunter of hepatocellular carcinoma

Yulang Jiang,
Yongxin Yu,
Ziyang Pan
et al.

Abstract: Ferroptosis is an iron ion-dependent, regulatory cell death modality driven by intracellular lipid peroxidation that plays a key role in the development of HCC. Studies have shown that various clinical agents (e.g., sorafenib) have ferroptosis inducer-like effects and can exert therapeutic effects by modulating different key factors in the ferroptosis pathway. This implies that targeting tumor cell ferroptosis may be a very promising strategy for tumor therapy. In this paper, we summarize the prerequisites and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 202 publications
0
5
0
Order By: Relevance
“…Acyl-CoA synthase long-chain family member 4 (ACSL4) catalyzes the conversion of AA or AdA to AA-CoA and AdA-CoA. Subsequently, lysine phosphatidylcholine acyltransferase 3 (LPCAT3) esterifies it to phosphatidylethanolamine (PE) to form AA-PE and AdA-PE, and finally oxidized to PE-AA-OOH and PE-AdA-OOH through polyunsaturated fatty acid lipoxygenase 15 (ALOX15) ( Jiang et al, 2024 ).…”
Section: The Mechanism Of Ferroptosismentioning
confidence: 99%
“…Acyl-CoA synthase long-chain family member 4 (ACSL4) catalyzes the conversion of AA or AdA to AA-CoA and AdA-CoA. Subsequently, lysine phosphatidylcholine acyltransferase 3 (LPCAT3) esterifies it to phosphatidylethanolamine (PE) to form AA-PE and AdA-PE, and finally oxidized to PE-AA-OOH and PE-AdA-OOH through polyunsaturated fatty acid lipoxygenase 15 (ALOX15) ( Jiang et al, 2024 ).…”
Section: The Mechanism Of Ferroptosismentioning
confidence: 99%
“…In particular, several studies have suggested that aspirin is involved in the modulation of ferroptosis in many diseases, including chronic kidney disease and cancer [183][184][185][186]. Most importantly, the modulation of ferroptosis by aspirin has been suggested as a mechanism for the treatment of different untreated cancers, anticancer drug resistance, and metastasis [187][188][189][190][191][192][193][194]. Similarly, iron and other transition metal complexes of aspirin and aspirin-based compounds have been suggested as new anticancer agents [195].…”
Section: Interactions Of Aspirin (Acetylsalicylic Acid) and Its Glucu...mentioning
confidence: 99%
“…A major unexplored area of great importance in pharmacology and medicine is the effects of aspirin and ACM, as well as their iron complexes, on ferroptosis, which is a recently identified type of programmed cell death based on iron-catalysed lipid peroxidation damage of cell membranes [179][180][181][182][183][184]. Ferroptosis has been identified in almost all diseases, including cancer and neurodegeneration [179][180][181][182][183][184][185][186][187][188][189][190]. Several preliminary investigations have already implicated aspirin in the process of ferroptosis via different mechanisms [192][193][194].…”
Section: Future Studies and Limitations On The Role Of Aspirin In Iro...mentioning
confidence: 99%
“…The regulation of amino acids that synthesize GSH raw materials, the content and activity of GSH synthase, the subcellular spatiotemporal distribution of GSH, and the mechanism of GSH catabolism and degradation can significantly affect GSH content and influence human GSH homeostasis [ 6 ]. The GSH/SLC7A11/GPx4 axis is the most important defense axis of ferroptosis, and SLC7A11, as the upstream of the ferroptosis pathway, serves as the raw material for the synthesis of GSH through the uptake of cystine, whereas GSH, through the action of GPx4, is able to reduce lipid peroxides on the plasma membrane to lipids and alcohols, thus protecting cells from ferroptosis [ 7 , 8 ]. More than that, GSH is also involved in the regulation of cell metabolism, proliferation, and gene expression.…”
Section: Introductionmentioning
confidence: 99%